Long-Term Potentiation Enhances Neuronal Differentiation in the Chronic Hypoperfusion Model of Rats - Takeuchi, Hayato; Kameda, Masahiro; Yasuhara, Takao; Sasaki, Tatsuya; Toyoshima, Atsuhiko; Morimoto, Jun; Kin, Kyohei; Okazaki, Mihoko; Umakoshi, Michiari; Kin, Ittetsu; Kuwahara, Ken; Tomita, Yosuke; et al. (Frontiers in Aging Neuroscience, 2018)
Several reports have shown that long-term potentiation (LTP) per-se effectively enhances neurogenesis in the hippocampus of intact animals. If LTP can enhance neurogenesis in chronic hypoperfusion, this approach could potentially become a new therapeutic strategy for the restoration of cognitive function and for prevention from deterioration of mild cognitive impairment. Using an in-vivo LTP model of rats, we examined whether LTP per-se can enhance neurogenesis in hypoperfusion rats that underwent permanent bilateral common carotid artery occlusion (permanent 2-vessel occlusion: P2VO). High frequency stimulation (HFS) in the subacute phase after P2VO enhanced hippocampal cell proliferation and neurogenesis. However, most enhanced cell proliferation and neurogenesis was seen in the hypoperfusion rats that received HFS and for which LTP could finally be induced. In contrast, the same effect was not seen in the LTP induction in the chronic phase. The present findings, which reveal that most enhanced neurogenesis was seen in hypoperfusion rats for which LTP could be finally induced, could explain the ability of LTP-like activities such as learning paradigms and environmental stimuli to increase the rate of neurogenesis in the hippocampus even under hypoperfusion conditions. Moreover, the present findings, which reveal that LTP induction in the chronic phase after P2VO could not effectively enhance neurogenesis in the hypoperfusion rats, could indicate that patients with mild cognitive impairment (MCI) and even middle-aged healthy control individuals should start LTP-like activities as early as possible and continue with these activities to prevent age-related deterioration of hippocampal function.